Analisis Kebutuhan Penilaian Capaian Literasi STEM Peserta Didik dalam Pembelajaran Biologi - Maisyarah Ayu Budi Ningrum; Yosi Laila Rahmi (JURNAL EKSAKTA PENDIDIKAN (JEP), 2021)
STEM literacy in education aims to be able to prepare students to be able to compete in the world of education in the world of work in the future. The benefit of STEM Literacy is that it makes students more skilled in all areas including science, technology, mathematics, and engineering. In ad- dition, STEM literacy can also make students improve their critical thinking skills and become crea- tive, logical, innovative, productive and relate directly to real conditions. This study aims to analyze the needs of students' STEM literacy achievement assessment in learning biology. The type of research used is descriptive, with data collection techniques carried out by conducting observations and inter- views. The results showed that biology learning has been implemented based on STEM literacy, stu- dents are still less enthusiastic in reading, students are more interested in learning related to technol- ogy, teachers do not know the assessment of students' STEM literacy achievement in biology learning.